(untitled) - Landes, David S. (Cambridge, MA., 1983)
More than a decade after the publication of his dazzling book on the cultural, technological, and manufacturing aspects of measuring time and making clocks, David Landes has significantly expanded Revolution in Time. In a new preface and scores of updated passages, he explores new findings about medieval and early-modern time keeping, as well as contemporary hi-tech uses of the watch as mini-computer, cellular phone, and even radio receiver or television screen. While commenting on the latest research, Landes never loses his focus on the historical meaning of time and its many perceptions and uses, questions that go beyond history and involve philosophers and, possibly, theologians and literary folk as well.
Keywords: Đồng hồ,Clocks and watches; Lịch sử,History